Molecular principles of the spontaneous mutagenesis in DNA - Brovarets, Ol’ha (Lviv Polytechnic Publishing House, 2016)
Reported results are crucial for understanding of the microstructural mechanisms of the spontaneous transitions and transversions, since they allow us to explain, from the one side, the origin of the mutagenic tautomers at the separation of the DNA strands before its replication and, from the other side, in what way occurs the adaptation of the incorrect purine·pyrimidine, purine·purine and pyrimidine·pyrimidine wobble pairs to the enzymatically competent sizes in the recognition pocket of the high-fidelity DNA-polymerase.
Keywords: spontaneous point mutagenesis; incorporation and replication errors; tautomerisation; pairs of nucleotide bases; enzymatically-competent conformation; hydrogen bond; quantum chemistry